2012
DOI: 10.1007/s10661-012-3001-6
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption properties of Morus alba L. for Cd (II) ions removal from aqueous solutions

Abstract: The abundantly available industrial waste product Morus alba L. pomace (MAP) is one of the cost-effective biosorbent for removal of metal ions from aqueous solutions. Hence, in the present study, we aimed to test the ability of MAP to remove Cd(II) ions through batch biosorption process. Firstly, MAP was characterized using several techniques, and then the influence of various experimental parameters such as initial pH of the aqueous solution, initial Cd(II) concentration, contact time, MAP concentration, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Biosorption-the ability of certain biomaterials to bind and concentrate heavy metals, even from diluted aqueous solutions-offers a technically feasible and economical alternative to remove heavy metals from industrial waste and natural water streams (Pahlavanzadeh et al 2010;Serencam et al 2013). The capacity to biosorb Ni(II) from aqueous solutions has been analyzed in some microorganisms as well as in biomaterials such as agroindustrial, forestry, and fishery by-products and biowastes (Gialamouidis et al 2009;Malkoc 2006;Pradhan et al 2005;Suazo-Madrid et al 2011;Vinod et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Biosorption-the ability of certain biomaterials to bind and concentrate heavy metals, even from diluted aqueous solutions-offers a technically feasible and economical alternative to remove heavy metals from industrial waste and natural water streams (Pahlavanzadeh et al 2010;Serencam et al 2013). The capacity to biosorb Ni(II) from aqueous solutions has been analyzed in some microorganisms as well as in biomaterials such as agroindustrial, forestry, and fishery by-products and biowastes (Gialamouidis et al 2009;Malkoc 2006;Pradhan et al 2005;Suazo-Madrid et al 2011;Vinod et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The high initial sorption phase was then followed by a gradual increase to approach equilibrium in about 60 min. Similarly, Noeline et al (2005) also a reported 60-min time for Pb adsorption equilibrium from an aqueous solution (10 mg L −1 ) by polymerized banana stem, and Serencam et al (2013) also reported a 60-min equilibrium time for Cd from 50 mg L −1 Cd solution with Morus alba L. pomace. In contrast, Tan and Xiao (2009) attained a quicker Cd adsorption equilibrium (in 30 min) when ground wheat stems were exposed to 22.5 mg L −1 Cd solution.…”
Section: Effect Of Contact Time and Initial Metal Concentrationmentioning
confidence: 73%
“…The high initial sorption phase was then followed by a gradual increase to approach an equilibrium in about 60 min. Similarly, Noeline et al (2005) have also reported 60 min time for Pb adsorption equilibrium from an aqueous solution (10-10 mg/dm 3 ) by polymerized banana stem and Serencam et al (2013) reported 60 min equilibrium time for Cd from 50 mg/ dm 3 Cd solution with Morus alba L. pomace. While Tan and Xiao (2009) attained quicker Cd adsorption equilibrium (in 30 min) when ground wheat stems was exposed to 22.5 mg/dm 3 Cd solution.…”
Section: Effect Of Contact Time and Initial Concentrationsmentioning
confidence: 82%